Protective Effect of Hydroxychloroquine on Renal Damage in Patients with Lupus Nephritis: Data from LUMINA, a Multiethnic U.S. Cohort - Pons-Estel, Guillermo J. (2009)
OBJECTIVE: To assess if hydroxychloroquine can delay renal damage development in lupus nephritis patients. METHODS: Lupus nephritis patients (n=256) from LUMINA (n=635), a multiethnic cohort of African Americans, Hispanics and Caucasians, age ≥16 years, disease duration ≤5 years at baseline (T0) were studied. Renal damage was defined per the SLICC Damage Index (≥1 of the following lasting at least six months: estimated/measured glomerular filtration rate <50%, 24-hour proteinuria ≥3.5 g and/or end-stage renal disease, regardless of dialysis or transplantation). Patients with renal damage before T0 were excluded (n=53). The association between hydroxychloroquine use and renal damage (as defined, or omitting proteinuria) was estimated using Cox proportional regression analyses adjusting for potentially confounders. Kaplan-Meier survival curves based on hydroxychloroquine intake or World Health Organization (WHO) Class glomerulonephritis were also derived. RESULTS: Sixty-three (31.0%) of 203 patients developed renal damage over a mean (standard deviation) disease duration of 5.2 (3.5) years. The most frequent renal damage domain item was proteinuria. Hydroxychloroquine-takers (79.3%) exhibited a lower frequency of WHO Class IV glomerulonephritis, lower disease activity and received lower glucocorticoid doses than non-takers. After adjusting for confounders, hydroxychloroquine was protective of renal damage occurrence in full (HR=0.12; 95% CI 0.02-0.97; p=0.0464) and reduced (HR=0.29; 95%CI 0.13-0.68; p=0.0043) models. Omitting proteinuria provided comparable results. The cumulative probability of renal damage occurrence was higher in hydroxychloroquine non-takers and in WHO Class IV glomerulonephritis (p<0.0001). CONCLUSIONS: After adjusting for possible confounding factors the protective effect of hydroxychloroquine in retarding renal damage occurrence in SLE is still evident.